Applied data mining - Xu, Guandong; Zong, Yu.; Yang, Zhenglu (Boca Raton : CRC Press, 2013)
"In past decades, data mining has witnessed substantial advances by efforts from various communities. On the other hand, new research questions and practical challenges are continuously presented due to newly emerging topics and applications within the various fields closely related to human daily life, e.g. social media and social networking. This book aims to bridge the gap between the existing research and application progresses in traditional data mining and the latest advances in newly emerging information services. It explores the extension of well-studied algorithms and approaches into these new research arenas"--
Includes bibliographical references and index.
Keywords: Data mining; COMPUTERS / Database Management / Data Mining; COMPUTERS / Machine Theory; MATHEMATICS / Advanced